Apolipoprotein E Genotype and Sex Influence Glucose Tolerance in Older Adults: A Cross-Sectional Study - Angela J. Hanson; William A. Banks; Hector Hernandez Saucedo; Suzanne Craft (Dementia and Geriatric Cognitive Disorders Extra, 2016)
Background: Glucose intolerance and apolipoprotein ε4 allele (E4+) are risk factors for Alzheimer's disease (AD). Insulin sensitizers show promise for treating AD, but are less effective in E4+ individuals. Little is known about how the APOE genotype influences glucose metabolism. Methods: Cross-sectional analysis of 319 older adults who underwent oral glucose tolerance tests; a subset had insulin, amyloid beta (Aβ42), and Mini Mental Status Examination. Glucose and insulin patterns with respect to cognitive diagnosis, E4 status, and sex were examined with analysis of covariance and Pearson correlation. Results: People with cognitive impairment had higher fasting insulin levels. E4 status did not affect fasting glucose values, whereas men had higher fasting glucose levels than women. E4+ men had the lowest and E4+ women had the highest glucose levels, compared to E4- groups; insulin did not differ by sex or E4 group. E4 status and sex moderated correlations between metabolic measures and AD risk factors including age and Aβ. Conclusions: Insulin resistance was associated with cognitive impairment, and sex, E4 status, and glucose values are interrelated in older adults at risk of AD. Understanding glucose metabolism for different APOE and sex groups may help elucidate differences in therapeutic responses.